Highly active antiretroviral therapy of cognitive dysfunction and neuronal abnormalities in SCID mice with HIV encephalitis - Cook-Easterwood, Jennifer (2007)
Our objective was to determine if highly active antiretroviral therapy (HAART), previously shown to ameliorate several pathological features of HIV encephalitis (HIVE) in a SCID mouse model, would also reduce additional established pathological features of HIV: cognitive dysfunction, TNF-α production, and reduced MAP-2 expression. SCID mice with HIVE and control mice inoculated with uninfected monocytes were administered HAART or saline. The HIV pathological features evaluated included astrogliosis, viral load, neuronal apoptosis, MAP-2 expression, mouse TNF-α mRNA production and learning acquisition and retention. HAART reduced the HIV induced viral load, and the astro- and microgliosis as previously observed; this effect was extended to HIV-induced increases in TNF-α mRNA production. In contrast, although HIV produced the cognitive deficits previously observed and also decreased MAP-2 expression in the area surrounding injected HIV-infected human monocytes, HAART did not attenuate these effects. Interestingly, there was no neuronal apoptosis evident at the time-point reflecting the above pathology. The results of this study combined with previous reports indicate that HAART reduces TNF-α mRNA, viral load and astrogliosis; however, HAART does not improve HIV-induced cognitive dysfunction or MAP-2 decreases. These results suggest that viral load, astrogliosis, TNF-α and apoptosis are not prominent in the pathogenesis of early functional deficits related to decreased MAP-2 expression or cognitive dysfunction in HIVE in SCID mice.